2007
DOI: 10.1139/x07-089
|View full text |Cite
|
Sign up to set email alerts
|

Growth and foliar nutrition of juvenile western hemlock and western redcedar plantations on low- and medium-productivity sites on northern Vancouver Island: response to fertilization and planting density

Abstract: A factorial trial was established to examine the effects of planting density and fertilization on the growth of western redcedar (Thuja plicata Donn ex D. Don) and western hemlock (Tsuga heterophylla (Raf.) Sarg.) on nutrient-poor (CH) sites and nutrient-medium (HA) sites. Two levels of NPK fertilization were crossed with three levels of planting density (500, 1500, and 2500 stems/ha). Fifteen years after establishment and 10 years after the last fertilizer application, height, individual stem volume increment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…There have been a number of replicated, meso-scale experimental fertilization trials in Western Canada extending, at time of writing, up to nearly 4 decades across different forest types and Biogeochemical Ecosystem Classification (BEC, Meidinger and Pojar 1991) zones (e.g. Brockley 2007, record case of 25 fold over controls by Negrave et al (2007) in a y.o. cedar-hemlock coastal forest.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of replicated, meso-scale experimental fertilization trials in Western Canada extending, at time of writing, up to nearly 4 decades across different forest types and Biogeochemical Ecosystem Classification (BEC, Meidinger and Pojar 1991) zones (e.g. Brockley 2007, record case of 25 fold over controls by Negrave et al (2007) in a y.o. cedar-hemlock coastal forest.…”
Section: Introductionmentioning
confidence: 99%
“…With mean annual precipitation near 3500 mm, these perhumid rainforests are at the extreme range in rainfall for the Pacific west coast (Carpenter et al, 2014). The evidence for P constraints outlined in this trial have been substantiated by fertilizer studies along northern Vancouver Island (Blevins et al, 2006;Negrave et al, 2007), but other areas in the Pacific Northwest have shown more variation in growth response to added P (Radwan et al, 1991;Mainwaring et al 2014). Lower precipitation levels or differences in soil mineralogy could mediate rates of soil podzolization and reductions in Pi so the full regional extent of these presumed P deficiencies should be examined and tested more thoroughly.…”
Section: Discussionmentioning
confidence: 53%
“…With mean annual precipitation near 3500 mm, these perhumid rainforests are at the extreme range in rainfall for the Pacific west coast (Carpenter et al, 2014). The evidence for P constraints outlined in this trial have been substantiated by fertilizer studies of very similar perhumid forests along northern Vancouver Island (Blevins et al, 2006;Negrave et al, 2007), but other areas in the Pacific Northwest have shown more variation in growth response to added P (Radwan et al, 1991;Mainwaring et al, 2014). Lower precipitation levels or differences in soil mineralogy could mediate rates of soil podzolization and reductions in P i so the full regional extent of these presumed P deficiencies should be examined and tested more thoroughly.…”
Section: Regional Significance Of P Deficienciesmentioning
confidence: 52%